Bandwidth aspects in second generation current conveyors - Alves, Luis Nero
This paper discusses bandwidth problems associated with second–generation current conveyors. In particular, our work is centered in high-capacitance applications, especially for wireless optical links and applied physics. We discuss techniques for improving bandwidth in these CCII, and develop a new CCII structure with larger bandwidth than traditional circuits. These circuits are then compared in terms of their noise and dynamic range characteristics.